Conductive Silver Grid Electrode for Flexible and Transparent Memristor Applications. (28th December 2020) - Han, Xu; Xu, Ruixue; Sun, Bowen; Xu, Jing; Hong, Wang; Cai, Guofa; Qian, Kai
Abstract: Transparent nonvolatile memory fabricated on flexible substrates is expected to meet the requirement of integrated flexible transparent circuits. Here, a simple route to prepare flexible transparent memristors is presented. Flexible transparent conducting Ag grids with low sheet resistance are self‐assembled on polyethylene terephthalate (PET) substrate, and the WO3 dielectric layer is selectively deposited on the Ag grids via a low‐cost cathodic electrodeposition method under ambient condition. Finally, the Au/WO3 /Ag grids/PET device exhibits fair good optical transmittance in the visible region, low operating voltages, fast switching speed, and long retention time against electric and mechanical stimulus. Therefore, a universal approach is demonstrated for flexible transparent memristors application by combining Ag grids electrode with cathodic electrodeposition technology. Abstract : A flexible transparent memristor is fabricated by combining a self‐assembled metal grid electrode with a cathodic electrodeposition technique. The as‐fabricated Au/WO3 /Ag grid/polyethylene terephthalate memory device shows excellent performance in terms of low operating voltage (+0.75 V/−0.5 V),  decent mechanical durability, fast switching speed, and long retention time against electric and mechanical stimulus.